Fast Terminal Integral Synergetic Control for Variable Speed Wind Turbine - Diaz-Diaz, M; Rajendran, S (Institute of Electrical and Electronics Engineers Inc., 2022)
This work focuses on designing a nonlinear controller for maximum wind energy extraction with minimum stress on the drive train for variable speed wind turbines. A two-mass model is utilized for modeling the wind turbine. It can deal with aerodynamic nonlinearities and structural flexibility. Initially, conventional sliding mode controllers are adapted. However, these controllers have high oscillations on the drive train and control input. Further, to overcome the above issues, a fast terminal synergetic control, fast integral synergetic control, and fast terminal integral synergetic control with a wind estimator are proposed. Initially, a mathematical model was employed to test the controllers, and then a Fatigue, aerodynamics, structures, and turbulence 600 kW model was used to validate the existing and proposed control schemes. A comparative analysis has been conducted, and the results conclude that the fast terminal integral synergetic control improves the power capture with transient load reduction. © 2022 IEEE.